DECODING SUSPICIOUS WEB THREAT INTERACTIONS: ADVANCED DETECTION AND ANALYSIS - Umair Riaz; Zaigham Riaz; Muhammad Zulkifl Hasan; Muhammad Zunnurain Hussain (Spectrum of Engineering Sciences, 2025)
The security of Web is a significant issue for personal, corporate, and state users in the context of digitalization. With all kinds of activities related to the Internet growing, different types of threats also emerge, including phishing, malware, ransomware, and others which threaten personal information, funds, and critical system structures. The present paper discusses the principal threats that are inherent in the web environment, the effects of these threats, and protection means. Phishing is a common kind of social engineering that aims at making the target release relevant information. Viruses and worms in its broad sense include Malware, which sneaks into systems to corrupt, steal or delete important information. Ransomware is a type of virus that encrypts a victim’s files and asks for payment for the decryption key while drive-by downloads is another virus that installs itself on a victim’s computer from compromised websites without the victim knowing. With spoofing and man-in-the-middle attacks, data integrity is not preserved while SQL injection and cross-site scripting are aimed at controlling web applications in order to control databases. Ddos-attack or Distributed Denial of Service attack on services knocks them off balance by flooding them with traffic. Minimizing risks entails keeping oneself posted on the latest developments, updating the software, locking passwords in the cyber world, using a two factor identification key, and making sure that different strains of technology have back up copies of the materials that have been tampered with. Adhering to security practices and being alert to new threats is vital for an organization to have a safe online existence. Hence, this study emphasizes on the need to adopt appropriate measures of evaluating web threats in order to have safe interactions.